Multiple Moving Force Identification Based on Bridge Bending Moment Influence Lines - Qian, C.Z.; Chen, C.P.; Dai, L.M. (Journal of Applied Nonlinear Dynamics, 2026)
Identification of the moving forces on a bridge is essential to bridge design and management. A new method for identifying the time varying axle loads is presented in this research using the bending moment influence line. Based on the theorem of modal superposition and taking the damping force into consideration, several modal accelerations can be obtained from measured accelerations of the bridge at several sections. Based on the d’Alembertian theory, the inertia force of the bridge is expressed as a distributed load. Using the bending moment influence lines of the bridge, the moving force contributing to the moment and the inertia force are obtained. The formulation about flexural moment and moving force is obtained correspondingly. An optimization method is used to find the solution of the equations, and then the moving forces can be obtained at any given time. Examples show that the method has a high accuracy in identifying moving forces even though there are more than one time varying forces. By applying the proposed method, information regarding the moving forces can be obtained without solving the dynamic equation, resulting in an efficient model for applications in engineering.